An extension of the core product model for the maturity management of the digital mock up: use of graph and knowledge to describe mechanical parts. (1st January 2014) - Herlem, Guillaume; Adragna, Pierre-Antoine; Ducellier, Guillaume; Durupt, Alexandre
Reverse engineering (RE) of mechanical parts consists in creating a 3D virtual model using data that are often gathered by 3D measurement systems like laser scanners. The resulting point cloud is then transformed into a geometrical model. The purpose of RE activity is to make maintenance or redesign operations easier. The boundary of the literature is the component, isolated from its product assembly. Because of unreported on-field maintenance, a long time running in-use product may not reflect its digital mock-up (DMU) anymore. In order to maintain an efficient lifecycle, the changes made have to be considered. This paper focuses on the development of a knowledge-based RE methodology to support the DMU maturity management: to identify the maturity defaults, which correspond to unreported changes, in the CAD assembly model in order to make it matching the real product. That approach is supported by a core product model data model extension.